Exploring the aesthetic representation of Pinisi as the basis of urban experience (Department of Architecture Faculty of Engineering Universitas Indonesia, 2025)
This study explores the aesthetic representation of the Pinisi ship as the basis of an attractive urban space. In particular, it focuses on the aesthetic of a pedestrian bridge in the Sudirman Central Business District (SCBD), Jakarta. The study argues that the visual representation of the Pinisi ship as the epitome of indigenous sailing craft in Indonesia provides a cultural experience that attracts pedestrians, creating relations between the aesthetics of urban space and the overall visitor interest. This study aims to identify the elements of the Pinisi ship that are represented through aesthetic principles and analyse the relationship between representation and urban pedestrian experience. This study uses a qualitative method with a case study approach. Data sources were obtained through field observations, interviews, and discussions with stakeholders, such as governments, planners, and developers. The analysis of the pedestrian bridge shows the elements that define its aesthetic representations and spatial experience for the user, contributing to the knowledge regarding the importance of representation and attractiveness in public space.